Metformin prevents anti-osteogenic in vivo and ex vivo effects of rosiglitazone in rats - Sedlinsky, Claudia (2011)
Long-term treatment with the insulin-sensitizer rosiglitazone reduces bone mass and increases fracture risk. We have recently shown that orally administered metformin stimulates bone reossification and increases the osteogenic potential of bone marrow progenitor cells (BMPC). In the present study we investigated the effect of a 2-week metformin and/or rosiglitazone treatment on bone repair, trabecular bone microarchitecture and BMPC osteogenic potential, in young male Sprague-Dawley rats. Compared to untreated controls, rosiglitazone monotherapy decreased bone regeneration, femoral metaphysis trabecular area, osteoblastic and osteocytic density, and TRAP activity associated with epiphyseal growth plates. It also decreased the ex vivo osteogenic commitment of BMPC, inducing an increase in PPARγ expression, and a decrease in Runx2/Cbfa1 expression, in AMP-kinase phosphorylation, and in osteoblastic differentiation and mineralization. After monotherapy with metformin, with the exception of PPARγ expression which was blunted, all of the above parameters were significantly increased (compared to untreated controls). Metformin/rosiglitazone co-treatment prevented all the in vivo and ex vivo anti-osteogenic effects of rosiglitazone monotherapy, with a reversion back to control levels of PPARγ, Runx2/Cbfa1 and AMP-kinase phosphorylation of BMPC. In vitro co-incubation of BMPC with metformin and compound C-an inhibitor of AMPK phosphorylation-abrogated the metformin-induced increase in type-1 collagen production, a marker of osteoblastic differentiation. In conclusion, in rodent models metformin not only induces direct osteogenic in vivo and ex vivo actions, but when it is administered orally in combination with rosiglitazone it can prevent several of the adverse effects that this thiazolidenedione shows on bone tissue.